KOMODIFIKASI MEMORI DAN DIGITAL MOURNING DALAM REKONSTRUKSI KONTEN AI MEMORIAL SERVICE @selamanya_ai DI TIKTOK - Viersa Rosyada; Reni Shinta Dewi (Jurnal Komunikasi dan Kajian Media, 2026)
The phenomenon of artificial intelligence (AI)-based memory reconstruction marks a change in mourning practices in the digital communication space. This study aims to analyze how the reality of grief and the presence of deceased individuals are constructed through AI Memorial Service content produced by the business entity @selamanya_ai. The research data includes the main video, captions, and audience interactions in the comments section. This study uses John Fiske's semiotic analysis to identify codes of reality, representation, and ideology in visual and narrative content, which are then interpreted using Social Construction Theory and Computer-Mediated Communication (CMC). The results show that AI reconstruction utilizes gestures, facial expressions, voices, and visual framing to create an illusion of presence and emotional closeness, thereby representing memory and grief as a continuous symbolic experience. The findings also indicate a process of commodification of memory, in which the experience of grief is produced as digital content that can be consumed by the public. This study concludes that AI technology plays an active role in shaping a new social reality related to memory, death, and emotional relationships on social media